Cretaceous continental margin evolution revealed using quantitative seismic geomorphology, offshore northwest Africa. (17th May 2020) - Casson, Max; Calvès, Gérôme; Huuse, Mads; Sayers, Ben; Redfern, Jonathan
Abstract: The application of high‐resolution seismic geomorphology, integrated with lithological data from the continental margin offshore The Gambia, northwest Africa, documents a complex tectono‐stratigraphic history through the Cretaceous. This reveals the spatial‐temporal evolution of submarine canyons by quantifying the related basin depositional elements and providing an estimate of intra‐ versus extra‐basinal sediment budget. The margin developed from the Jurassic to Aptian as a carbonate escarpment. Followed by, an Albian‐aged wave‐dominated delta system that prograded to the palaeo‐shelf edge. This is the first major delivery of siliciclastic sediment into the basin during the evolution of the continental margin, with increased sediment input linked to exhumation events of the hinterland. Subaqueous channel systems (up to 320 m wide) meandered through the pro‐delta region reaching the palaeo‐shelf edge, where it is postulated they initiated early submarine canyonisation of the margin. The canyonisation was long‐lived ( ca . 28 Myr) dissecting the inherited seascape topography. Thirteen submarine canyons can be mapped, associated with a Late Cretaceous‐aged regional composite unconformity (RCU), classified as shelf incised or slope confined. Major knickpoints within the canyons and the sharp inflection point along the margin are controlled by the lithological contrast between carbonate and siliciclastic subcrop lithologies. Analysis of the base‐of‐slope deposits at the terminus of the canyons identifies two end‐member lobe styles, debris‐rich and debris‐poor, reflecting the amount of carbonate detritus eroded and redeposited from the escarpment margin (blocks up to ca . 1 km 3 ). The vast majority of canyon‐derived sediment (97%) in the base‐of‐slope is interpreted as locally derived intra‐basinal material. The average volume of sediment bypassed through shelf‐incised canyons is an order of magnitude higher than the slope‐confined systems. These results document a complex mixed‐margin evolution, with seascape evolution, sedimentation style and volume controlled by shelf‐margin collapse, far‐field tectonic activity and the effects of hinterland rejuvenation of the siliciclastic source. Abstract :